2012
DOI: 10.1021/bi3001903
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Energetic Effects of Charge Reversal Mutations of Poxvirus Topoisomerase IB

Abstract: A key aspect of the reaction mechanism of type IB topoisomerases is the controlled unwinding of DNA supercoils while the enzyme is transiently bound to one strand of the DNA duplex via a phosphotyrosyl linkage. In this complex, the mobile segment of the bound DNA downstream from the site of cleavage must rotate around the helical axis, requiring that interactions with the enzyme must break and reform multiple times during the course of removing supercoils. A crystal structure of variola virus type IB topoisome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Although all MCs migrated as single bands during agarose gel electrophoresis, they consisted of a Gaussian distribution of topoisomers when electrophoresis was performed using 5% polyacrylamide gels in the presence of 10 mM MgCl 2 , or using a 6% native gel in the presence of chloroquine (Figure 2 and Figure S1 of the Supporting Information ). 20 , 22 , 24 The 454 bp minicircle that lacked the specific site (MC ns ), as well as its corresponding highly supercoiled form MC ns* , followed the same topological distributions as MC sp and MC sp* .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although all MCs migrated as single bands during agarose gel electrophoresis, they consisted of a Gaussian distribution of topoisomers when electrophoresis was performed using 5% polyacrylamide gels in the presence of 10 mM MgCl 2 , or using a 6% native gel in the presence of chloroquine (Figure 2 and Figure S1 of the Supporting Information ). 20 , 22 , 24 The 454 bp minicircle that lacked the specific site (MC ns ), as well as its corresponding highly supercoiled form MC ns* , followed the same topological distributions as MC sp and MC sp* .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that cationic residues on vTopo interact with the negatively charged DNA backbone of the rotating DNA segment and impact the number of supercoils that are released per cleavage event. 21 , 22 , 36 A previously characterized vTopo mutant (K271E) was known to increase the number of supercoils that were removed per cleavage event and was a desirable mutant to test using MC sp2 . 22 Indeed, relaxation experiments with MC sp2 showed slower cleavage and fewer intermediates with K271E than with wild-type vTopo (compare panels B and C of Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations